Gene expression analysis identifies hypothetical genes that may be critical during the infection process of Xanthomonas citri subsp. citri - Laia, Marcelo Luiz de; Moreira, Leandro Marcio; Goncalves, Janaina Fernandes; Tiraboschi Ferro, Maria Ines [UNESP]; Pinto Rodrigues, Any Caroliny; Santos, Jessica Naiara dos; Felestrino, Erica Barbosa; Ferro, Jesus Aparecido [UNESP] (Univ Catolica De Valparaiso, 2019)
Background: Gene expression analysis via microarray is widely used in phytobacteria to validate differential gene expression associated with virulence or to compare biological profiles of wild type and mutant strains. Here, we employed DNA microarrays to study the early stages of the infection process (24, 72 and 120 h post-inoculation) of Xanthomonas citri subsp. citri (Xac) infecting Citrus sinensis to interrogate the expression profiles of hypothetical genes. Results: Under infective conditions, 446 genes were up-and 306 downregulated. Outstanding among genes upregulated during infection were those involved in synthesizing the Type 3 Secretion System and effectors, xanthan gum and quorum-sensing induction, and flagellum synthesis and regulation. Additionally, 161 hypothetical genes were up-and 100 were downregulated, 49 of which are known to have a significant biological role. To understand hypothetical gene co-regulation or -expression, nine expression profiles including 158 genes were identified during the three infection phases. Of these, 47 hypothetical genes were identified as having expression profiles associated with at least one connected to a gene associated with adaptation and virulence. Conclusions: Expression patterns of six differentially expressed genes were validated by quantitative reverse transcription polymerase chain reaction, thus demonstrating the effectiveness of this tool in global gene expression analysis in Xac. (C) 2019 Pontificia Universidad Catolica de Valparaiso. Production and hosting by Elsevier B.V. All rights reserved.
Keywords: Citrus sinensis; DNA microarrays; Gene expression; Hypothetical genes; Oligonucleotide Array Sequence Analysis; RT-qPCR; Transcriptome; Type III secretion systems; Virulence; Xanthan gum